ANSWER
y = 2x - 1
Step-by-step explanation
We want to find the equation that represents the data in the table in the form:
y = mx + b
where m = slope
b = y intercept
To do this, we have to first find the slope of the equation using the formula for slope:
![m=(y2-y1)/(x2-x1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/wt3vklmulg2853jxzclws9uvfaplhmpgv7.png)
where (x1, y1) and (x2, y2) are two sets of data points from the table.
Let us pick (0, -1) and (1, 1) as (x1, y1) and (x2, y2) respectively.
Therefore, the slope, m, is:
![\begin{gathered} m=(1-(-1))/(1-0)=(1+1)/(1)=(2)/(1) \\ m=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9zdeehmqcwfnp6ike99wqzn6bqce0thbz8.png)
Now, we use the point-slope method to find the equation:
![y-y1=m(x-x1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/w8833wq43gzv073odoa76ku9bunhdf4cj7.png)
Therefore, the equation is:
![\begin{gathered} y-(-1)=2(x-0) \\ y+1=2(x) \\ y+1=2x \\ y=2x-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uqkq2tmt3p0wufnb6j26wfp1j73hj9cay8.png)
That is the equation.